STUDIES ON THE ROLE OF DRIED ETHANOLIC EXTRACT OF AGARICUS BISPORUS IN THE TREATMENT OF DEPRESSION IN MICE - SUSHRUTA CHAKRABORTY; SANDIPAN SAU; ABHIK SI; SOUVIK BASAK; RIKU ROY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Depression is a widespread mental illness with an estimated 322+million people worldwide and one of the most frequent reasons for medical and physical disability. However, the standard treatments available are having side effects such as addiction, physical dependence, and to overcome the lacuna researchers are looking for natural remedies Thus our study aimed to investigate the anti-depressant effect of Agaricus bisporus (White button mushroom) in mice. Methods: The anti-depressant action of dried ethanolic extract of A. bisporus (EEAB) was evaluated in the Swiss albino mice by various models. After extraction and standardization of the white button mushroom the dose-dependent anti-depressant effect of the white button mushroom was determined. Further, with the best chosen dose, the chronic anti-depressant effect of the white button mushroom was carried out, and also to further substantiate the data brain bioamine estimation was done. Results and Discussion: Statistical analysis with EEAB 200 mg/kg and 400 mg/kg showed marked anti-depressant action in dose-dependent manner. The calibration of EEAB extract by high-performance liquid chromatography guided a determination that the presence stigmasterol. Brain estimation of the EEAB with 400 mg/kg dose displayed upregulation of Serotonin in the treated mice. Since Serotonin is a major neurotransmitter which is key role anti-depressant activity. Hence, the upregulation of Serotonin suggests that EEAB is having profound anti-depressant activity.